PERALATAN PERANG NICA DALAM MENGHADAPI PEJUANG PADA MASA REVOLUSI FISIK DI BALI TAHUN 1945 - 1950 - Ida Bagus Astika Pidada (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
[Title: The Nica War Equipment in Facing Patriots in Physical Revolution in Bali In 1945 – 1950] Giving up without the conditions of Lieutenant General H. Ter Poorten (Commander of the Dutch East Indies) on behalf of the United States Army in Indonesia to Liuetenant General Hiroshi Imamura (Japanese Army Leader). Since the Dutch East Indies government ended in Indonesia. At that time Dutch soldiers who were Japanese prisoners of war because they did not have time to flee to Australia were sent to the interior of Siam and Birma to clear forests and make bridges and railways. On August 15th 1945, Japan finally surrendered to allies. This defeat of Japan caused the captives of the Dutch to quickly hold preparatory exercises back to Indonesia. The arrival of the Dutch in Bali received resistance from the fighters under the leadership of Lieutenant Colonel I Gusti Ngurah Rai. Although the weapons possessed by fighters in Bali is limited but the struggle is long enough to survive. NICA in the face of fighters in Bali during the physical revolution has used modern war equipment such as: pipercub airplanes, lucked airplanes, motorbikes, jeeps, telephones, bren, mitraliur, stengun, mortar, lichthalon and others but not easy can beat him. This is because the fighters with the people in Bali are united.